EFFECTIVENESS OF PERFECT STUDYING OF FOREIGN LANGUAGES (Academicia Globe: Inderscience Research, 2023)
This article discusses the importance of perfect learning of foreign languages, effective methods used in teaching foreign languages to schoolchildren, and analyzes the results.